Inhibition of Foot-and-Mouth Disease Virus Replication by Hydro-alcoholic and Aqueous-Acetic Acid Extracts of Alhagi maurorum: Antiviral activity of of Alhagi maurorum against FMDV - Yasmin Shakiba,; Seyedeh Elham Rezatofighi,; Seyyed Mansour Seyyed Nejad,; Mohammad Roayaei Ardakani, (Iranian Journal of Pharmaceutical Sciences, 2018)
Foot-and-mouth disease (FMD) is a major infectious disease of cloven-hoofed animals that is caused by the FMD virus (FMDV). This disease has significantly adverse economic impacts; therefore, rapid control measures are urgent. Hydro-alcoholic and aqueous-acetic acid extracts of A. maurorum were prepared and their anti-FMDV activity was evaluated. Gas Chromatography–Mass Spectrometry (GC-MS) analysis of methanolic and ethanolic extracts was performed to find the likely active compounds of A. maurorum. The cytotoxicity of the extracts was assayed and the antiviral activity of them was evaluated by measuring the percentage of viable FMDV infected-cells via the MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide) assay at different stages of the virus replication cycle. The results indicated that the plant extracts exhibit antiviral activity against FMDV at all stages of the experiment, although the most significant effects were observed in virucidal and pre-treatment assays. GC-MS of the extracts resulted in the separation of 3 and 2 main peaks for the methanolic and ethanolic extracts respectively. The major compound was found to be 1, 2-Benzenedicarboxylic acid, diisooctyl ester. These findings represent the anti-FMDV activities of A. maurorum extracts at several stages of the virus replication cycle; therefore, it could be considered for the potential development of anti-FMDV therapeutics.